Exploring the efficacy of al-hijamah (wet cupping) in managing hypertension and dyslipidemia among Indonesian population: a meta-analysis - Aulya, Justika Usmadhani; Matondang, Asri Rizqi; Farahdina, Farahdina; Rizaliansyah, Ferdian; Samsu, Nur; Fajar, Jonny Karunia (Heart Science Journal, 2024)
BACKGROUND: In Indonesia, wet cupping therapy has been thoroughly investigated as a treatment for hypertension and dyslipidemia. Nevertheless, the outcomes across these studies are contradictory.OBJECTIVES: To appraise the effectiveness of wet cupping therapy in the management of hypertension and dyslipidemia among the Indonesian population.METHODS: We examined papers sourced from Google Scholar, the Indonesian Scientific Journal Database, and Garba Rujukan Digital until September 5, 2020. These papers investigated blood pressure and lipid profile levels both pre- and post-wet cupping treatment. The collective data underwent Z-test analysis to assess associations.RESULTS: In total, we included 26 papers examining the correlation between wet cupping therapy and blood pressure, as well as 16 papers assessing lipid profile levels. Our combined analysis revealed significantly reduced systolic blood pressure (MD: 13.86; 95% CI: 10.01, 17.71), diastolic blood pressure (MD: 6.31; 95% CI: 3.84, 8.79), and lower total cholesterol levels (MD: 21.56; 95% CI: 10.32, 32.80]) in the post-treatment group compared to the pre-treatment group. However, we were unable to elucidate the impact of wet cupping therapy on the concentrations of low-density lipoprotein and triglyceride.CONCLUSIONS: Wet cupping therapy exhibits potential efficacy in reducing blood pressure and total cholesterol levels among individuals in Indonesia.